Low rates of anti-recipient isohemagglutinins in ABO incompatible hematopoietic stem cell transplants. (February 2021) - Adkins, Brian D.; Andrews, Jennifer; Sharma, Deva; Hughes, Caitlin; Kassim, Adetola A.; Eichbaum, Quentin
Abstract: Introduction: Isohemagglutinins occur naturally and form in an 'opposite' (antigen-negative) pattern to a patient's ABO blood type. Patients undergoing minor and bidirectional ABO incompatible hematopoietic stem cell transplantation (HSCT) may demonstrate detectable antibodies against their native blood type. In this study, we sought to characterize the rates of such antibody formation and evaluate the clinical significance of our findings. Materials and Methods: An internal database of HSCT patients at an academic medical center was queried for ABO incompatible transplant patients from 2009-2019. Serum typing results, clinical histories, and laboratory data were compiled and reviewed. Results: A total of 182 minor and bidirectional ABO incompatible HSCT patients were identified. Anti-recipient isohemagglutinins were found in 9% (16/182) of the HSCT patients. The rate was higher in patients with minor incompatibility (12%: 15/127) versus bidirectional ABO incompatibility (2%: 1/55) (p = 0.04). No anti-recipient isohemagglutinins were identified in umbilical cord HSCT patients (0%: 0/7). Serologic agglutination reactions of recipient isohemagglutinins were overall mostly weak (13/16 weak + to 1+). There was a trend towards a higher rate of acute graft-versus-host-disease in patients with anti-recipient isohemagglutinins compared to those without (75% vs. 53%; p = 0.12), though not statistically significant. Rates of alloimmunization to minor red cell antigens were similar between the two groups. Few patients showed laboratory evidence of hemolysis at 12 months follow up. Discussion and conclusions: Anti-recipient isohemagglutinins occur at low rates in ABO incompatible HSCT and are significantly more common in minor ABO incompatible transplant compared to bidirectional transplants. Larger cohort studies are needed to better understand the relationship between anti-recipient isohemagglutinins and HSCT outcomes.